Trans-synaptic degeneration in the visual pathway: Neural connectivity, pathophysiology, and clinical implications in neurodegenerative disorders - Sharma, Samridhi; Chitranshi, Nitin; Wall, Roshana Vander; Basavarajappa, Devaraj; Gupta, Vivek; Mirzaei, Mehdi; Graham, Stuart L; Klistorner, Alexander; You, Yuyi (Survey of ophthalmology, 2022)
There is a strong interrelationship between eye and brain diseases. It has been shown that neurodegenerative changes can spread bidirectionally in the visual pathway along neuronal projections. For example, damage to retinal ganglion cells in the retina leads to degeneration of the visual cortex (anterograde degeneration) and vice versa (retrograde degeneration). The underlying mechanisms of this process, known as trans-synaptic degeneration (TSD), are unknown, but TSD contributes to the progression of numerous neurodegenerative disorders, leading to clinical and functional deterioration. The hierarchical structure of the visual system comprises of a strong topographic connectivity between the retina and the visual cortex and therefore serves as an ideal model to study the cellular effect, clinical manifestations, and deterioration extent of TSD. With this review we provide comprehensive information about the neural connectivity, synapse function, molecular changes, and pathophysiology of TSD in visual pathways. We then discuss its bidirectional nature and clinical implications in neurodegenerative diseases. A thorough understanding of TSD in the visual pathway can provide insights into progression of neurodegenerative disorders and its potential as a therapeutic target. [Display omitted]